PERANAN PENDIDIKAN DAN PELATIHAN PEGAWAI DALAM PENGEMBANGAN INDUSTRI KECIL DAN MENENGAH PADA DINAS PERINDUSTRIAN, PERDAGANGAN, KOPERASI DAN UKM KABUPATEN KUTAI - Rusdiana Rizeria (Magister Administrasi Publik FISIP Universitas Mulawarman, 2019)
The purpose of this study to describe and analyze the role of education and training in developing IKMs and explain the factors supporting and inhibiting at the Department of Industry, Pergadangan, Cooperatives and SMEs Kutai Barat. The research focused on the role of education and training of personnel in developing IKMs. This study is qualitative descriptive. Data was obtained through interviews, observation and document, and then analyzed using an interactive model. The results of the study explained that education and training can be increased knowledge, abilities, skills and work attitude of employees so instrumental in the development of IKMs include increased quality of programming development of IKMs, improve the effectiveness of programs, improve facilitation and improving product marketing IKMs, although the role of education and training has been applied with good but with limited results..Keyword: Education and Training, Civil Servants, IKM Development.